Treatment of infections caused by carbapenem-resistant Acinetobacter baumannii - Zhang, Siqin; Di, Lingfang; Qi, Yan; Qian, Xiang; Wang, Siwei (Frontiers in Cellular and Infection Microbiology, 2024)
Patients with severe carbapenem-resistant Acinetobacter baumannii (CRAB) infections currently face significant treatment challenges. When patients display signs of infection and the clinical suspicion of CRAB infections is high, appropriate treatment should be immediately provided. However, current treatment plans and clinical data for CRAB are limited. Inherent and acquired resistance mechanisms, as well as host factors, significantly restrict options for empirical medication. Moreover, inappropriate drug coverage can have detrimental effects on patients. Most existing studies have limitations, such as a restricted sample size, and are predominantly observational or non-randomized, which report significant variability in patient infection severity and comorbidities. Therefore, a gold-standard therapy remains lacking. Current and future treatment options of infections due to CRAB were described in this review. The dose and considerable side effects restrict treatment options for polymyxins, and high doses of ampicillin-sulbactam or tigecycline appear to be the best option at the time of initial treatment. Moreover, new drugs such as durlobactam and cefiderocol have substantial therapeutic capabilities and may be effective salvage treatments. Bacteriophages and antimicrobial peptides may serve as alternative treatment options in the near future. The advantages of a combination antimicrobial regimen appear to predominate those of a single regimen. Despite its significant nephrotoxicity, colistin is considered a primary treatment and is often used in combination with antimicrobials, such as tigecycline, ampicillin-sulbactam, meropenem, or fosfomycin. The Infectious Diseases Society of America (IDSA) has deemed high-dose ampicillin-sulbactam, which is typically combined with high-dose tigecycline, polymyxin, and other antibacterial agents, the best option for treating serious CRAB infections. A rational combination of drug use and the exploration of new therapeutic drugs can alleviate or prevent the effects of CRAB infections, shorten hospital stays, and reduce patient mortality.